2014
DOI: 10.1007/s13277-014-1812-5
|View full text |Cite
|
Sign up to set email alerts
|

Does carbon dioxide pneumoperitoneum enhance wound metastases following laparoscopic abdominal tumor surgery? A meta-analysis of 20 randomized control studies

Abstract: The mechanisms involved in the development of wound metastasis following laparoscopic abdominal tumor surgery remain unclear. The aim of this study was to accurately assess whether the duration of carbon dioxide pneumoperitoneum (CDP) during laparoscopic abdominal tumor surgery enhances wound metastases. We conducted a systematic review of PubMed, Cochrane Library, and Embase through December 2013 to identify animal experiments comparing wound recurrence between laparoscopic and gasless laparoscopic procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…[17][18][19][20] In 2014, a meta-analysis including 20 randomized control trials using animal models found that wound recurrence was not significantly higher in laparoscopic surgery compared to gasless laparoscopy (odds ratio [OR] 2.23; 95% confidence interval [CI], 0.90 -5.55; P = .08) or laparotomy (OR, 0.97; 95% CI, 0.031 -3.00; P = .08). 21 Furthermore, surgical technique and repeated reintroduction of trocars have also been proposed in the development of PSM. 10,17 The latter may lead to trauma and exposure to malignant cells, rendering the surrounding tissue susceptible to tumor implantation.…”
Section: Mechanism Of Recurrencementioning
confidence: 99%
“…[17][18][19][20] In 2014, a meta-analysis including 20 randomized control trials using animal models found that wound recurrence was not significantly higher in laparoscopic surgery compared to gasless laparoscopy (odds ratio [OR] 2.23; 95% confidence interval [CI], 0.90 -5.55; P = .08) or laparotomy (OR, 0.97; 95% CI, 0.031 -3.00; P = .08). 21 Furthermore, surgical technique and repeated reintroduction of trocars have also been proposed in the development of PSM. 10,17 The latter may lead to trauma and exposure to malignant cells, rendering the surrounding tissue susceptible to tumor implantation.…”
Section: Mechanism Of Recurrencementioning
confidence: 99%
“…Animal studies exploring the role of CO 2 gas in possible tumor spread have been conflicting; some have suggested that CO 2 pneumoperitoneum may increase wound and peritoneal metastases compared with laparotomy or gasless laparoscopy, [20][21][22] although other studies have failed to demonstrate a difference. 23,24 An additional consideration is whether the extent of resection differs between minimally invasive and open surgical approaches for radical hysterectomy. One single-institution study suggested that robotic surgery was associated with a higher rate of close surgical margins compared with open surgery, although only 20 cases were robotic and may have been performed during the robotic surgery learning curve.…”
Section: Reviewmentioning
confidence: 99%
“…This is not sufficient to be a causative factor for xenograft implantation and angiogenesis induction. Moreover, an impact of CO2 insufflation itself on tumor cell implantation is under debate [ 3 ]. Therefore, it seems to be more suitable to call this model as “Morcellation-induced parasitic myomas”.…”
Section: Main Textmentioning
confidence: 99%